Protecting Famous Trademarks: Legal Insights from the EV Electro Voice Case in Indonesia - Robiyatul Adawiyyah, Inni Isnaini; Indrawati, Septi (Journal of Judicial Review, 2024)
Trademark rights play a critical role in business, particularly in navigating global competition and safeguarding well-known brands. However, the principle of good faith in trademark registration is often exploited to mimic the fame of established trademarks. This study examines the prohibition of the registered trademark "EV ELECTROVOICE + Logo" as contested by the trademarks "EV and Logo" and "ELECTRO-VOICE," as outlined in Decision Number 83/Pdt.Sus-HKI/Merek/2023/PN Niaga Jkt.Pst. The research aims to analyze the legal rationale behind the court's decision and its implications for trademark protection in Indonesia, especially concerning the application of the first-to-file principle and the protection of well-known trademarks. Employing a normative juridical method, the study focuses on examining relevant legal norms and their application in practice. The findings reveal that the court nullified the “EV ELECTROVOICE + Logo” registration due to bad faith, as the registration was intended to leverage the reputation of well-known trademarks. This decision underscores the significance of maintaining good faith in trademark registration and highlights the influence of international law in securing rights for well-known trademarks. The study contributes to a deeper understanding of trademark law dynamics in Indonesia and sheds light on the decision's implications for protecting famous trademarks within the national legal framework. Ultimately, the research aims to enrich the comprehension of trademark law principles in Indonesia and provide insights for improving regulations to address the challenges of trademark protection in a globalized era.